1997
DOI: 10.1152/jappl.1997.82.4.1119
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine administration alters the response to inspiratory loading in oxygen-supplemented rats

Abstract: Based on recent studies, it has been suggested that free radicals are elaborated in the respiratory muscles during strenuous contractions and contribute to the development of muscle fatigue. If this theory is correct, then it should be possible to attenuate the development of diaphragm fatigue and/or delay the onset of respiratory failure during loaded breathing by administering a free radical scavenger. The purpose of the present experiment was, therefore, to examine the effect of N-acetylcysteine (NAC), a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…In rats subjected to 60 -70% IRL, MAP fell to ϳ25 mmHg (post-IRL) and, after removal of the load, to Ͻ10 mmHg despite 15 min of mechanical ventilation (11), a result consistent with irreversible cardiac injury. In decerebrate rats subjected to IRL, MAP decreased from approximately 150 to 39 mmHg over the final few minutes before respiratory arrest (46); smaller falls were observed in two other studies (45,47). Borzone et al (12,13) noted that rats breathing air and subjected to IRL failed within 10 min because of hypoxemia and hypotension unless they were given supplementary O 2 .…”
Section: Discussionmentioning
confidence: 92%
“…In rats subjected to 60 -70% IRL, MAP fell to ϳ25 mmHg (post-IRL) and, after removal of the load, to Ͻ10 mmHg despite 15 min of mechanical ventilation (11), a result consistent with irreversible cardiac injury. In decerebrate rats subjected to IRL, MAP decreased from approximately 150 to 39 mmHg over the final few minutes before respiratory arrest (46); smaller falls were observed in two other studies (45,47). Borzone et al (12,13) noted that rats breathing air and subjected to IRL failed within 10 min because of hypoxemia and hypotension unless they were given supplementary O 2 .…”
Section: Discussionmentioning
confidence: 92%
“…Most studies in the literature have used a high inspiratory load, demonstrating a time-to-task failure that ranged from few minutes to 1 h maximum (2,47). However, recent studies have shown that IRB with a moderate load differs from that with a high load (21,42,43,51,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…NAC is an antioxidant that acts both as a free radical scavenger and as a source of cysteine for glutathione synthesis. During IRB, NAC delays fatigue (52), increases the time to respiratory arrest (47), decreases the delayed diaphragmatic injury (at 3 days after severe IRB) (23), restores diaphragmatic glutathione levels (47), and decreases intradiaphragmatic protein carbonyl formation (5). In our model NAC administration blunted protein carbonyl formation in the diaphragm, decreased IRB-induced cytokine upregulation, and in parallel decreased P38, ERK1/2, and NF-B/p65 subunit phosphorylation, suggesting that ROS is a stimulus for MAPKs and NF-B activation and hence cytokine production in response to IRB.…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%
“…It has been well established that production of ROS and lipid peroxidation products is elevated in the ventilatory muscles during strenuous muscle contractions (36,37,39). Supinski et al (36) investigated the association between increased lipid peroxidation and the development of muscle fatigue in dogs.…”
Section: Discussionmentioning
confidence: 99%